The Effect of Service and Competence on The Performance of The Commissioners of The Code of Ethics Enforcement Commission of Muhammadiyah University of Makassar - Sulaiman; Edi Jusriadi; Andi Jam'an (LP2M IAIN Palopo, 2025)
This study aims to determine the influence of service and competence on the performance of commissioners of the Code of Ethics Enforcement Commission at Muhammadiyah University of Makassar. This research method is quantitative. Based on the research results and discussions regarding the influence of service and competence on the performance of commissioners of the Code of Ethics Enforcement Commission at Unismuh Makassar, it is concluded that service has a positive and significant effect on commissioner performance. This is proven by the hypothesis test: the calculated t-value for service is 4.408 > the table t-value of 0.166, with a sig. value of 0.004 < the significance level (0.05). Competence has a positive and significant effect on commissioner performance. This is proven by the hypothesis test: the calculated t-value for commissioners is 8.557 > the table t-value of 0.166, with a sig. value of 0.000 < the significance level (0.05).